Enhancement of p-type gas-sensing performances of NiO nanoparticles prepared by precipitation with RuO2 impregnation - Kruefu V. (2017)
In this work, 0-1.00 wt% Ru-loaded nickel oxide nanoparticles were synthesized by the chemical precipitation/impregnation methods and systematically characterized for gas-sensing applications. Characterizations by electron microscopy, X-ray diffractometry, X-ray photoemission spectroscopy showed that primary particles were face-centered-cubic structure of NiO and RuO 2 nanoparticles were dispersed within larger NiO NPs. Nitrogen adsorption studies also revealed that specific surface area of RuO 2 /NiO nanoparticles increased with increasing Ru content. Gas-sensing measurement showed that increasing Ru loading content considerably improved C 2 H 5 OH response and selectivity against H 2 S, NO 2 , SO 2 , H 2 , and NH 3 at an operating temperature of 350 °C. In particular, the NiO sensor with the highest Ru content of 1.00 wt% showed a high p-type sensor response of 35.9-2000 ppm C 2 H 5 OH at 350 °C, which was about three times as high as that of unloaded one. Therefore, RuO 2 loading by impregnation is an effective mean to improve the gas-sensing performances of p-type NiO-based gas sensors.